Wilayah Kajian dan Filsafat Ekonomi Islam - Khoiruddin Nasution (Millah: Journal of Religious Studies, 2002)
This article attempts to study of both the area of Islamic economy and the  philosophy of Islamic economy. In this paper, the researcher uses the data from  al Qur 'an, prophet tradition, alfiqh and other resources, and then it will he analyzed by the hermeneutic approach The result of this paper, is that the area  of Islamic economy including in social affairs (mu'amalah) field, while the philosophy of Islamic economy is the ideas of Islamic economy that presents  the system of economy which guarantee the justice and the equality for every  body who participates in economy activities.